Introduction to digital media design transferable hacks, skills and tricks - Hardy, David Leicester (2022)
A hands-on exploration of digital design methods and tools, providing enough information to quickly learn the basics across web, interaction, interface, user experience, augmented and virtual reality design, as well as animation and motion graphics. Contemporary digital designers work across programs, platforms and disciplines, but there's not always enough time to become an expert in everything before having to get stuck in to your next project. This is a hands-on approach to take you through the building blocks, common skills and hacks across all forms of digital design so you understand the fundamentals and can start creating straight away. Includes exercises, full-colour examples and instructions so you can make connections and become familiar with topics from: User Experience (UX), User Interface (UI) and Interaction Design (IxD)- Animation and motion graphics- Virtual (VR), augmented (AR) and mixed reality.
Introduction: convergence with tech, divergence of media -- User interface and digital design -- User experience design -- Animation and motion graphics -- Interaction design -- Design for the Web -- Emerging technologies -- Epilogue.
Includes bibliographical references and index.
Keywords: Digital media -- Design; Computer graphics; User interfaces (Computer systems) -- Design; Graphical user interfaces (Computer systems) -- Design